Estimation of Resistin and Adiponectin Levels in Iraqi Women with Hypothyroidism - Ahmed, Haneen Tariq; Hussein, Saba Zuhair (Iraqi Journal of Science, 2025)
Hypothyroidism, the most common clinical condition associated with thyroid hormone deficiency, can pose significant health risks. Adipokines, such as resistin and adiponectin, are hormones secreted by adipose tissue. Research has shown that lipid profiles and adipokine levels are altered in individuals with thyroid dysfunction. The aim of this study was to evaluate serum levels of adiponectin and resistin in Iraqi women newly diagnosed with hypothyroidism and to investigate the relationship between such levels of thyroid hormones and lipid profile. The study included one hundred women in the age 20-50 years old. They were split into two groups: fifty patients with recently diagnosed hypothyroidism and fifty healthy women who are as controls. In contrast to the healthy group, the hypothyroidism group's concentrations of fasting blood glucose (FBG), body mass index (BMI), total cholesterol (TC), thyrotropin (TSH), very low-density lipoprotein (VLDL), triglyceride (TG), low-density lipoprotein (LDL), and resistin all significantly increased, while thyroxine (T4), triiodothyronine (T3), high-density lipoprotein (HDL), and adiponectin levels decreased. An important positive correlation was observed between adiponectin and T4 and T3. In terms of diagnostic performance, adiponectin and resistin showed high AUC values of 0.915 and 0.975, respectively, in the case of comparing hypothyroidism to the control group. In conclusion, hypothyroid patients had lower adiponectin and higher resistin levels, indicating these parameters could be a diagnostic marker for hypothyroidism patients because of excellent discrimination between hypothyroidism patients and healthy controls.